PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA MELALUI KEPUASAN KERJA KARYAWAN PADA AMERTA EXPERIENCE - I Made Aryana; Ni Ketut Dewi Irwanti; I Putu Santika (Fakultas Ekonomi Universitas Warmadewa, 2025)
This study aims to analyze the influence of transformational leadership and organizational culture on employee performance through job satisfaction at Amerta Experience. The population in this study consists of all 100 employees of Amerta Experience. The sampling technique used is a census or saturated sample, involving 99 respondents. The analysis techniques include validity test, reliability test, classical assumption test, and path analysis. The results show that: (1) transformational leadership has a positive and significant effect on job satisfaction, (2) organizational culture has a positive and significant effect on job satisfaction, (3) transformational leadership has a positive and significant effect on employee performance, (4) organizational culture has a positive and significant effect on employee performance, (5) job satisfaction has a positive and significant effect on employee performance, (6) job satisfaction acts as a mediating variable in the influence of transformational leadership on employee performance, and (7) job satisfaction mediates the influence of organizational culture on employee performance at Amerta Experience. The study suggests that the management of Amerta Experience should enhance transformational leadership, organizational culture, job satisfaction, and employee performance.